The satirical map is a medium for criticism of the contemporary Arab Maghreb reality among Moroccan artists - Salah, Haifa Ebn Hadj (Journal of Humanities & Social Sciences, 2022)
During the recent timeframe, what has become the Arab Maghreb plastic artist’s goal during the recent period is foregrounding, through cartographic works that mimic the reality of the Maghreb Arab world, the plethora of the latter’s matters. This is to be done either via critical artwork that may reach a level of sarcasm in certain stances, or via criticizing reality in which the Arab world witnesses ideological and socio-cultural conflicts. That image is nothing more than a multi-faceted area of research that defines the Maghreb identity and represents the intellectual, cultural and social features of the corresponding society. Ergo, various artists tried to transmit the Maghreb reality through different images in such a manner that they entered the realm of social critique and satire. Yet, the intensity of criticism varies from an artist to another, for it is gauged according to his/her cultural and social backgrounds; adding to that his/her national sense of belonging. Indeed, the plastic artist has ventured in the game of geographic leveling of countries, and even of the map as a whole. Thus, they rendered the general makeup of the image a mimesis of his/her design which was both critical and awareness-oriented. Satirical maps, then, saw the light and waxed a plastic medium that transmits and critiques the modern Maghreb world.
Keywords: map and society; criticism of reality; irony and sarcasm; contemporary Maghreb reality; contemporary Maghreb Arab plastic practice